GREENHOUSE GAS EMISSIONS AND LAND USE ISSUES RELATED TO THE USE OF BIOENERGY IN INDONESIA - Muhrizal Sarwani; Neneng Laela Nurida; Fahmuddin Agus (Jurnal Penelitian dan Pengembangan Pertanian, 2013)
Biofuel use is intended to address the ever-increasing demand for and scarcer supply of fossil fuels. The recent Indonesia government policy of imposing 10% mixing of biodiesel into petroleum-based diesel affirms the more important biofuel role in the near future. Palm oil, methane from palm oil mill effluent (POME) and animal wastes are the most prospective agricultural-based biofuels. The production and use of palm oil is interlinked with land use and land use change (LULUC), while the use of methane from POME and animal wastes can contribute in reducing emissions. The current European Union (EU) and the potential United States (US) markets are imposing biodiesels’ green house gas (GHG) emission reduction standards (ERS) of 35% and 20%, respectively relative to the emissions of petroleum-based diesel based on using the lifecycle analysis (LCA). EU market will increase the ERS to 50% starting1 January 2017, which make it more challenging to reach. Despite controversies in the methods and assumptions of GHG emission reduction assessment using LCA, the probability of passing ERS increases as the development of oil palm plantation avoid as much as possible the use of peatland and natural forests. At present, there is no national ERS for bioenergy, but Indonesia should be cautious with the rapid expansion of oil palm plantation on existing agricultural lands, as it threatens food security. Focusing more on increasing palm oil yield, reducing pressure on existing agricultural lands for oil palm expansion and prioritizing the development on low carbon stock lands such as grass- and shrublands on mineral soils will be the way forward in addressing land scarcity, food security, GHG emissions and other environmental problems. Other forms of bioenergy source, such as biochar, promise to a lesser extent GHGemission reduction, and its versatility also requires consideration of its use as a soil ameliorant.